2017
DOI: 10.1016/j.jpba.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of Populus type propolis

Abstract: Herein, we propose rapid and simple spectroscopic methods to determine the chemical composition of propolis derived from various Populus species using a metabolomics approach. In order to correlate variability in Populus type propolis composition with the altitude of its collection, NMR, IR, and UV spectroscopy followed by OPLS was conducted. The botanical origin of propolis was established by comparing propolis spectral data to those of buds of various Populus species. An O2PLS method was utilized to integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Specific resonances attributable to glycerol esters (such as 1,3-di-p-coumaryl-2-acetyl-glycerol and 1,3-diferulyl-p-coumarate-glycerol) were given by the presence of signals in the zone 4.2-5.3 ppm (glycerol moiety), an area crowded with several overlapping signals, and a singlet resonance for methyl groups at 2.05 ppm. The presence of the acetyl groups and the ester groups were also confirmed by 13 C-NMR spectrum due to the presence of signals in the area between 160 and 170 ppm, the portion of glycerol, instead, gives signals at 63-71 ppm, the methyl groups of acetyl at 19.7 and 21.9 ppm in agreement with the literature data ( Figure 4) [25]. The definition of the type of glycerol ester was given with LC-MS orbitrap.…”
Section: Nuclear Magnetic Resonance (Nmr)supporting
confidence: 89%
See 2 more Smart Citations
“…Specific resonances attributable to glycerol esters (such as 1,3-di-p-coumaryl-2-acetyl-glycerol and 1,3-diferulyl-p-coumarate-glycerol) were given by the presence of signals in the zone 4.2-5.3 ppm (glycerol moiety), an area crowded with several overlapping signals, and a singlet resonance for methyl groups at 2.05 ppm. The presence of the acetyl groups and the ester groups were also confirmed by 13 C-NMR spectrum due to the presence of signals in the area between 160 and 170 ppm, the portion of glycerol, instead, gives signals at 63-71 ppm, the methyl groups of acetyl at 19.7 and 21.9 ppm in agreement with the literature data ( Figure 4) [25]. The definition of the type of glycerol ester was given with LC-MS orbitrap.…”
Section: Nuclear Magnetic Resonance (Nmr)supporting
confidence: 89%
“…The total flavones and flavonols (TFF) were estimated according to an aluminum chloride method following [63]. For the calibration curve, four standard solutions of quercetin in 80% ethanol (25,50,100, and 200 µg/mL) were prepared (y = 0.0099x -0.055; R 2 = 0.9999). A 0.5 mL portion of standard solutions was separately mixed with 1.5 mL of 95% ethanol, 0.1 mL of 10% AlCl 3 in water (w/v), 0.1 mL of 1 M potassium-acetate, and 2.8 mL of 80% ethanol.…”
Section: Total Phenolic Content Total Flavones and Flavonols And Frmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the main flavonoids found were pinocembrin (3), pinobanksin (1), pinobanksin-3-O-acetate (4), chrysin (2), quercetin (26), kaempferol (25) pinocembrin-7-methyl ether (27) and galangin (9) (Figure 1), while benzoic (28), ferulic (7), caffeic (5), 3,4-dimethoxycinnamic (29), cinnamic (21) acids were the most abundant phenolic acids. [54][55][56][57][58][59][60][61][62][63][64] However, other authors demonstrated that Croatian propolis contain phenolic acid esters such as CAPE (8), benzyl caffeate (12), benzyl coumarate (30) and cinnamic acid esters. [64 -66] On the another hand, Sobočanec et al [67] have reported the presence of flavonoids only in propolis samples from Continental Croatia.…”
Section: Southern European Coastmentioning
confidence: 99%
“…Maceration was adapted, the method was described by Anđelković, et al [22]. About 1 g of propolis powdered was cooled at -20 ° C, then materials were placed in a Erlenmeyer flask, 10 ml solvent (methanol: water, 80:20) was added.…”
Section: Extraction By Macerationmentioning
confidence: 99%